Rietveld quantitative phase analysis of non-stoichiometric cordierite synthesised from mainly talc and kaolin: Effect of sintering temperature - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Ariffin, Ahmad (Trans Tech Publications, Switzerland., 2011)
Link to publisher's homepage at www.ttp.net/